2014
DOI: 10.1002/smll.201300798
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Modified MoS2 Nanoflakes for Surface Enhanced Raman Scattering

Abstract: Though the SERS effect based on pristine MoS2 is hardly observed, however, the plasma treated MoS2 nanoflakes can be used as an ideal substrate for surface enhanced Raman scattering. It is proved that the structural disorder induced generation of local dipoles and adsorption of oxygen on the plasma treated MoS2 nanosheets are the two basic and important driven forces for the enhancement of Raman signals of surface adsorbed R6G molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 35 publications
(65 reference statements)
5
131
0
Order By: Relevance
“…This is because surface modification creates stronger interaction between the 2D materials and the analyte molecules, resulting in enhanced Raman intensity. For instance, plasma treated MoS 2 showed enhanced SERS performance with very high suppression of background signals, attributed to the formation of surface defects caused by the introduction of gaseous species . There is another report in which.…”
Section: D Inorganic Nanomaterials For Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because surface modification creates stronger interaction between the 2D materials and the analyte molecules, resulting in enhanced Raman intensity. For instance, plasma treated MoS 2 showed enhanced SERS performance with very high suppression of background signals, attributed to the formation of surface defects caused by the introduction of gaseous species . There is another report in which.…”
Section: D Inorganic Nanomaterials For Sensingmentioning
confidence: 99%
“…A detailed investigation on the surface properties of MoS 2 nanoflakes, plasma treated MoS 2 and pristine MoS 2 on the enhancement of the Raman spectra of R6G molecules has been conducted . The plasma treated MoS 2 led to the generation of local dipoles and oxygen adsorption on the MoS 2 layer, where the structural disorder induced local dipole and oxygen adsorption provided enhanced Raman scattering.…”
Section: D‐transition Metal Chalcogenides For Sensingmentioning
confidence: 99%
“…Two Raman enhancement mechanisms, i.e., charge transfer and dipole–dipole coupling, may co‐occur on MoS 2 nanosheets. Later, Sun et al investigated the SERS effect of oxygen/argon plasma treated MoS 2 nanosheets for Rhodamine 6G (R6G) molecules ( Figure a) . It was shown that structural disorders were generated by the plasma bombardment process, leading to the generation of local dipoles and adsorption of oxygen at ambient atmosphere.…”
Section: Tmd Nanosheets and Their Other Composite‐based Sensorsmentioning
confidence: 99%
“…These functionalization and surface treatments will modify the Fermi level of graphene and thus affect Raman scattering intensity of molecules on graphene through charge transfer resonance conditions [44]. Surface treated MoS 2 shows enhanced Raman intensities of R6G molecules by one order of magnitude compared with pristine MoS 2 flakes [45]. The introduction of defects in T-MoS 2 samples changes the local surface properties of MoS 2 nanoflakes, such as creating the local dipoles, which give rise to the enhancement of Raman signals of R6G molecules and absorbance of the oxygen in ambient air to dope holes in MoS 2 , resulting in the enhanced charge transfer effect between R6G and MoS 2 .…”
Section: Raman Enhancement Mechanism Of Two-dimensional Materialsmentioning
confidence: 99%